Defining physical literacy: making sense of a promiscuous concept. Issue 1 (27th December 2021) - Bailey, Richard
Abstract: The term physical literacy (PL) has become widely used in policy and practice discourses, engaging sport, physical activity, and physical education communities. Yet, despite its popularity, the term has taken many forms, encompassing different definitions, aims, and content. So, there is no single account, and this has led some to question the concept's current capacity to act as the basis of a coherent programme. Previous writers have reviewed definitions of PL. This article has a different goal: to consider the ways definitions are used, and how they relate to, or differ from, each other. It imports a conceptual framework for thinking about definitions from the philosophy of education. In doing so, the paper seeks to clarify some of the ambiguities within discussions of PL. It goes on to examine the uses and abuses of philosophy within the PL literature.